Factors Influencing Coastal Flooding from Akurala to Godagama in Sri Lanka - Wickramasooriya, Ashvin; Ravihari, G. (Media Konservasi, 2025)
Over the past decade, the Southwest coast of Sri Lanka has experienced recurrent coastal floods, particularly in the stretch from Akurala to Godagama. This study, spanning from 2010 to 2020, seeks to unravel the factors influencing these floods, filling a void in existing research on the subject. Employing topographic maps, field observations, and bathymetric data from the Lanka Hydraulic Institute and Coastal Conservation Department, the research delves into geomorphological features and elevation variations in the study area. Findings indicate that high elevation in the Ambalangoda to Akurala and Godagama to Hikkaduwa regions contributes to coastal flooding, as these areas are elevated above the mean sea level. The bathymetric analysis exposes closely spaced contours and steep slopes, exacerbating flooding when waves collide with the coastline. The absence of mangroves amplifies the impact, distinguishing the study area from its neighbouring regions. Socioeconomic consequences include road closures, accidents on the Galle-Colombo main road in 2020, and adverse effects on fisheries and tourism. Environmental impacts encompass coastal erosion, degraded water quality, coral bleaching, and saltwater intrusion. While artificial structures like rock barriers mitigate flooding, the study underscores the interplay of land morphology, bathymetry, land use, and climate influencing coastal flooding along the Akurala to Godagama coast.